Assessment of Indigenous Knowledge and Its Relevance for Livestock Production: the case of North Gondar zone: Amhara Region, Ethiopia (International Journal of Scientific Research and Management (IJSRM), 2018)
The study was conducted in North Gondar Zone, Amhara region Ethiopia, to explore the various indigenous knowledge systems practiced in livestock production by small holder farmers. Both qualitative and quantitative data were collected from primary and secondary data sources. Qualitative data that helped to assess indigenous knowledge practices in the study area were collected through personal observation, and focus group discussions. In addition to this semi-structured questionnaires were distributed to 120 Households spread across the three districts of different PA administrative to collect relevant data. The data collected through questioner was organized and analyzed by using SPSS (version 20). The study revealed that a combination of crop residue and natural pasture is common sources of feed for most (45.8 %) of respondents. The indigenous knowledge regarding livestock production is considered as old as domestication of various livestock species. With regard to feed treatment practices, most (51.7%) of the farmers in the area treat the animal feed by using common salt in order to increase food palatability by the animals. Ethno-veterinary medicines is one of the common practice by households in North Gondar Zone. Even though most (65%) of households prefer modern disease treatment, about 78.3 % of farmers are using cultural medicine for treating different livestock diseases The main reason for using cultural medicine by farmers in the area is it’s easily availability, cheapest cost and its practical applicability. The major constraint of indigenous knowledge utilization in north Gondar zone is the resistance Development agents (28.3%) followed by other administrative bodies (22.5%) in the region. There is a high risk of extinction of indigenous knowledge if it is not documented. To avoid this loss, emphasis should be given on developing indigenous knowledge systems and documenting this unique knowledge into the mainstream knowledge. In addition to this, research should be done on the various methods of ethno-veterinary medicine and document the effective ones for use by the future generations. Moreover, research from a gender perspective is needed to document specialized ethno-veterinary knowledge not only of cattle but also of small stock such as sheep and chickens. It is important that livestock farmers share ideas on traditional knowledge with modern veterinarians in order to optimize productive capacity of herds and enhance sustainable rural livelihoods.